Three Transducers Embedded into One Single SiC Photodetector: LSP Direct Image Sensor, Optical Amplifier and Demux Device - Vieira, M.; Louro, P.; Fernandes, M.; Vieira, M. A.; Fantoni, A.; Costa, J. (IntechOpen, 2011)
None